2021
DOI: 10.1038/s41467-021-22929-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant oncolytic virotherapy for personalized anti-cancer vaccination

Abstract: By conferring systemic protection and durable benefits, cancer immunotherapies are emerging as long-term solutions for cancer treatment. One such approach that is currently undergoing clinical testing is a therapeutic anti-cancer vaccine that uses two different viruses expressing the same tumor antigen to prime and boost anti-tumor immunity. By providing the additional advantage of directly killing cancer cells, oncolytic viruses (OVs) constitute ideal platforms for such treatment strategy. However, given that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
(41 reference statements)
1
24
1
Order By: Relevance
“…Moreover, a Maraba-based OV, MAGE-A3, is currently being tested in phase 1/2 studies (NCT02285816/NCT02879760). A recent study suggested that OVs can be co-administered with antigenic peptides in personalized anti-cancer vaccines to target patient-specific mutations [ 106 ]. However, even though OVs have been approved by the FDA and achieved certain efficacy in some patients, the resulting increase in type I IFNs can be problematic.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…Moreover, a Maraba-based OV, MAGE-A3, is currently being tested in phase 1/2 studies (NCT02285816/NCT02879760). A recent study suggested that OVs can be co-administered with antigenic peptides in personalized anti-cancer vaccines to target patient-specific mutations [ 106 ]. However, even though OVs have been approved by the FDA and achieved certain efficacy in some patients, the resulting increase in type I IFNs can be problematic.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…An alternate use of OV alongside CAR T cell therapy is to utilise genetically modified OVs to induce target antigen expression in the tumour. This has been achieved in solid tumour immunisation regimes via the use of OVs encoding target antigens or by administering the OV alongside antigenic peptides [ 114 , 115 , 116 ]. The ability of these OVs to induce significant antigen-specific T cell responses opens the possibility of using OVs to ectopically express any antigens in tumours in the attempt to aid CAR T cell recognition, solving the problems with suitable antigen choice in solid tumours [ 114 , 115 , 116 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…This has been achieved in solid tumour immunisation regimes via the use of OVs encoding target antigens or by administering the OV alongside antigenic peptides [ 114 , 115 , 116 ]. The ability of these OVs to induce significant antigen-specific T cell responses opens the possibility of using OVs to ectopically express any antigens in tumours in the attempt to aid CAR T cell recognition, solving the problems with suitable antigen choice in solid tumours [ 114 , 115 , 116 ]. This principle was demonstrated in preclinical studies, wherein the surface CD19 antigen was delivered by OV vectors to solid tumours, resulting in efficient targeting by anti-CD19 CAR T cell therapy [ 117 , 118 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…Transgenes are coding sequences engineered to be expressed by oncolytic viruses (and bacteria) for the purpose of modulating cellular gene expression [95]. Examples of transgenes include: cytokines [70], chemokines [87], inhibitors of immune checkpoints [79,104], bi-specific T cell engagers [105,106], tumor antigens [107], and targets for chimeric antigen receptor T cells (CAR-T) [108,109]. Of particular promise is granulocyte-macrophage colony-stimulating factor (GM-CSF) [95,110].…”
Section: Combinatorial Oncolytic Viral Oncotherapiesmentioning
confidence: 99%